A dense and uniform colored alumina ceramic and a preparation method thereof

A controlled sintering process using Al2O3, rare earth oxides, and a glass phase binder addresses the issues of color uniformity and density in alumina ceramics, resulting in high-performance, uniformly colored alumina ceramics with enhanced mechanical and thermal properties.

CN118878308BActive Publication Date: 2024-12-13HEBEI HUICI ELECTRONIC TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411378378.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-13
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Traditional methods for preparing colored alumina ceramics result in poor color uniformity, durability, and density, leading to uneven coloring and reduced lifespan due to environmental issues and mechanical mixing inefficiencies.

Method used

A dense and uniform colored alumina ceramic is prepared using Al2O3 powder, a compounded rare earth oxide sintering aid, and a glass phase as a molten binder, with a controlled sintering process to ensure optimal coloring and grain growth, achieving a volume density of ≥3.85 g/cm³ and flexural strength of ≥400 MPa.

Benefits of technology

The method produces alumina ceramics with high performance, good coloring uniformity, and fineness, offering excellent mechanical and thermal properties, suitable for various applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118878308B_ABST
    Figure CN118878308B_ABST
Patent Text Reader

Abstract

The invention discloses a dense and uniform colored alumina ceramic and a preparation method thereof. 2 O 3 The powder is used as the main raw material, a composite rare earth oxide sintering aid is introduced, and a glass phase is added as a molten binder, and a green ceramic body is obtained through batching, dry pressing or casting steps in sequence, and a colored alumina ceramic is prepared after sintering. The present invention adjusts the sintering temperature of the ceramic material to ensure that the colorant does not volatilize, and at the same time ensures the nucleation and growth of the grains during the sintering process. The prepared alumina ceramic material has high performance, good coloring, uniformity and fineness, and the volume density of the obtained alumina ceramic is ≥3.85g / cm 3 , flexural strength ≥400MPa, thermal conductivity ≥22W / (mk), and has good market application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic materials, and in particular relates to a dense and uniform colored alumina ceramic and a preparation method thereof. Background Art

[0002] Alumina ceramics have excellent mechanical properties, such as high strength, high hardness, wear resistance, metallic luster after polishing and no allergic effect on the human body. In recent years, they have gradually become the new favorite of high-end decorative materials such as artificial gemstones, watch cases, watch chains, and mobile phone cases. Traditional high-purity alumina ceramics are white after sintering. With the continuous expansion of the application range of alumina ceramic materials, single-color alumina ceramics are difficult to meet people's growing demand for them. Therefore, the research on colored alumina ceramics has gradually entered the public's field of vision.

[0003] The preparation of traditional colored ceramics generally uses the method of pouring glaze to color the ceramics, or directly mechanically mixes the coloring pigment with alumina powder, and then forms and sinters it to finally form colored ceramics. However, although these two methods satisfy the public's pursuit of ceramic colors to a certain extent, they have a series of disadvantages. For example, the pouring glaze coloring method not only has environmental problems, but also faces the shortcomings of durability. The colored alumina ceramics prepared by the simple mechanical mixing process have poor color uniformity, poor density and uniformity in the later sintering process, which ultimately leads to uneven color and density of ceramic products, and a low lifespan, which directly affects people's user experience.

[0004] Therefore, developing a colored alumina ceramic and how to improve the performance of the ceramic while introducing other colored components has become one of the research topics of many researchers. Summary of the invention

[0005] In view of the above technical problems, the present invention aims to provide a dense and uniform colored alumina ceramic, which overcomes the problems in the prior art that the glaze colored ceramics have poor durability and the mechanically mixed alumina ceramics have poor colorant uniformity, resulting in uneven coloring of the products, and the added colorant has a great influence on the strength of alumina. The present invention uses Al2O3 powder as the main raw material, introduces a compounded rare earth oxide sintering aid, and adds a glass phase as a molten binder. A green porcelain body is obtained by a dry pressing or tape casting ceramic forming process, and colored alumina ceramics are prepared after sintering. The present invention can adjust the sintering temperature of the alumina ceramic by adjusting the amount of the molten binder, so that the colorant is colored at its optimal coloring temperature, and at the same time ensures the nucleation and growth of the grains in the sintering process. The prepared alumina ceramic material has high performance, good coloring, uniformity and fineness, and the volume density of the obtained alumina ceramic is ≥3.85g / cm 3 , flexural strength ≥400MPa, thermal conductivity ≥22W / (mk), and has good market application prospects.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A dense and uniform colored alumina ceramic comprises the following components in parts by weight:

[0008] 90~99.5 parts of alumina, 50~70 parts of anhydrous ethanol, 0.5~2 parts of sintering aid, 5~10 parts of molten binder, 0.5~2 parts of colorant, 0.2~1 parts of binder, and 0.5~2 parts of dispersant.

[0009] As a limitation of the present invention:

[0010] (i) The sintering aid is a mixture of erbium oxide and ytterbium oxide in a mass ratio of 1:1.

[0011] (ii) The molten binder is aluminum-lithium-silicon glass powder, and its preparation process is carried out in the following steps:

[0012] S1, preparation of sol: add 90mL of ethanol to a beaker, slowly add 30g of tetraethoxysilane to the ethanol, stir with a stirrer at room temperature to form a uniform silicon precursor solution; add 30mL of deionized water and 1mL of nitric acid dropwise as an acid catalyst, continue stirring for 1h to form a uniform silica sol;

[0013] S2. Adding aluminum precursor: dissolving 10 g aluminum isopropanol in 20 mL ethanol to form a uniform aluminum precursor solution, slowly adding the aluminum precursor solution dropwise to the silica sol, and continuing stirring for 1 h to allow the aluminum sol to be uniformly mixed and undergo hydrolysis and condensation reactions to form a composite sol containing aluminum;

[0014] S3, adding lithium precursor: dissolving 2 g of lithium nitrate in 4 mL of deionized water to obtain a lithium precursor solution; slowly adding the lithium precursor solution dropwise to the composite sol, stirring continuously for 30 min, so that the lithium ions are evenly distributed in the sol, to obtain a lithium-containing composite sol;

[0015] S4. Rare earth doping: prepare a rare earth solution: dissolve 3 g of erbium oxide and 2 g of ytterbium oxide in dilute nitric acid to obtain a rare earth nitrate solution; slowly add the rare earth nitrate solution to the lithium-containing composite sol, and continue stirring for 2 hours to obtain a mixed solution;

[0016] S5, placing the obtained mixed solution in an electric constant temperature air drying oven and aging it at 40°C for 48 hours to make it gel-like, and then raising the temperature of the drying oven to 100°C and drying it for 10 hours to obtain a powdered glass powder precursor containing rare earth elements;

[0017] S6. Place the obtained precursor into a muffle furnace and sinter it according to the following process:

[0018] The first stage: heating from room temperature to 110 °C at a heating rate of 2 °C / min, and keeping the temperature for 150 min;

[0019] The second stage: heating from 110 ℃ to 400 ℃ at a heating rate of 2 ℃ / min, and keeping the temperature for 150 min;

[0020] The third stage: heating from 400 °C to 800 °C at a heating rate of 2 °C / min, keeping the temperature for 150 min, cooling to room temperature with the furnace, and obtaining the sintered product;

[0021] S7. The sintered product is ball-milled at 300 r / min for 10 h using a planetary ball mill. After the ball milling is completed, the obtained glass powder is sieved through a 200-mesh sieve and the product is collected, which is the molten binder.

[0022] The molten binder of the present invention is doped with rare earth ions (Er 3+ and Yb 3+ ), the rare earth compounds Er2O3 and Yb2O3 are uniformly dispersed in the sol and formed by chemical dissolution. 3+ and Yb 3+ ions; in the hydrolysis and condensation reactions of the sol-gel process, rare earth ions are captured in the formed gel network. In the subsequent drying and sintering process, the rare earth ions are gradually and evenly embedded in the glass matrix structure to form local structural distortion [Er 3+ and ions have a larger ionic radius (Er 3+ About 0.89 Å, Yb 3+ About 0.86 Å, compared to Al 3+ 0.54 Å and Si 4+ 0.26 Å) will introduce local lattice stress and distortion], which can change the physical and chemical properties of the glass, such as adjusting the refractive index and dielectric constant of the glass.

[0023] The molten binder is prepared by a sol-gel method, in which a three-dimensional network structure is formed by preparing a sol-gel. After gelation, the gel is aged for a period of time to further remove the solvent and volatile by-products, thereby improving the strength and stability of the gel. The aged gel is slowly dried at an appropriate temperature to remove the residual solvent. During this process, the temperature should be kept from rising too fast to prevent the gel from cracking or generating pores. The dried gel is sintered in a high-temperature furnace to remove organic matter and residual solvent, thereby further densifying the structure of the material and uniformly dispersing the rare earth elements in the aluminum-lithium silicate glass network at high temperature to form a doped glass powder.

[0024] As we all know, the fewer the sintering components of alumina ceramics, the less interference there is in the sintering growth process, and the better the thermal conductivity and mechanical properties of alumina ceramics. The sintering difficulty of pure white alumina ceramics is lower than that of alumina ceramics with multiple components because of the small number of components and less interference. Since the sintering temperature of alumina ceramics is relatively high and the melting temperature of the colorant is relatively low, if the two are sintered together during the sintering process, the colorant is easy to volatilize, which will not only directly affect the coloring color of the sintered ceramics, but also cause the density and porosity of the sintered ceramics to decrease due to the volatilization during the sintering process. In addition, this process will interfere with the nucleation and growth of alumina grains, reducing the performance of the ceramic material. The present invention introduces a molten binder into the formula, which, on the one hand, plays a role in regulating the sintering temperature of alumina ceramics during the sintering process of ceramic materials, and on the other hand, cooperates with the composite rare earth oxides in the ceramic components, thereby not only overcoming the problem of easy volatility and color difference after the introduction of coloring materials, but also solving the problems of poor uniformity and poor density caused by the interference of the heterogeneous introduction of coloring materials on the grain growth of alumina sintering process.

[0025] In the present invention, the amount of molten binder added is relatively important. Although adding too much can reduce the sintering temperature of alumina ceramics, it will lead to reduced mechanical properties and thermal stability of alumina ceramics; adding too little will limit the range of lowering the sintering temperature and affect the coloring effect of the colorant.

[0026] (iii) The colorant is a metal carbonate, a transition metal oxide, etc.

[0027] (iv) The binder is at least one selected from polyvinyl alcohol, polyvinyl butyral ester, hydroxypropyl methylcellulose and ethyl cellulose.

[0028] (V) The dispersant is selected from at least one of acrylate, propylene glycol methyl ether acetate, polyvinyl pyrrolidone, BYK, and triethyl phosphate.

[0029] The present invention also provides a method for preparing dense and uniform colored alumina ceramics, which is carried out in the following steps in sequence:

[0030] 1) Ingredients:

[0031] Weigh Al2O3 powder, sintering aid, colorant, molten binder, adhesive and dispersant in proportion into a ball mill, add anhydrous ethanol and mill for 30 minutes at a speed of 200-300 r / min, with a ball-to-material ratio of 1:3;

[0032] 2) Molding:

[0033] The molding step is carried out by the following ① dry pressing method or ② casting method:

[0034] ① Dry pressing method: the slurry obtained in step 1) is placed in a low-temperature oven at 60-90°C for drying, the dried slurry is collected and ground, the ground powder is passed through a 50-200 mesh sieve, and then the sieved powder is collected and bagged, and placed in a grinding tool and dry pressed at 200 MPa to form a colored alumina ceramic green body, with a disc diameter of 30 mm;

[0035] ② Casting method: After degassing, pour the ceramic slurry obtained in step 1) into a hopper, set the casting thickness to 150 μm, cast on a casting machine to obtain a wet blank, ventilate, heat and dry in the casting machine to obtain a raw ceramic strip, cut and stack to obtain a colored alumina ceramic green body;

[0036] 3) Sintering: The ceramic green body formed in step 2) is placed in a high-temperature sintering furnace and sintered at 1200° C. for 4 hours to obtain colored alumina ceramics.

[0037] As a limitation of the preparation method of the present invention, in step 3), the heating rate of the sintering heating process is 3°C / min.

[0038] The sintering process affects the growth of molten binder, rare earth oxides and alumina grains. Therefore, the sintering temperature, time and heating rate will affect the ceramic formation and performance of alumina ceramics. In the sintering heating process of the present invention, the non-ferrous alumina ceramic green body will undergo microscopic changes such as powder bonding growth, gradual melting of the molten binder and full filling of the body gap. In the gradual melting process, the rare earth oxides not only serve as sintering aids, but are also important optically active ions. 3+ and Yb 3+ Ions can absorb light of specific wavelengths (such as infrared light) and emit visible light through a conversion luminescence mechanism. They can be combined with other colorants (such as metal oxides) to adjust the color and transparency of ceramic materials. When rare earth elements and colorants are added to alumina ceramics, the presence of aluminum-lithium-silicon glass powder helps to evenly distribute these elements.

[0039] In addition, the rare earth oxide of the present invention will not react adversely with the colorant during the sintering process, but can stabilize the chemical state of the colorant to prevent the degradation or unevenness of the color. In addition, the present invention can achieve accurate control and optimization of color by controlling the concentration of rare earth elements and sintering conditions, thereby improving the diversity and application breadth of products. This ceramic has excellent color stability and uniformity, and can be used in architectural ceramics, decorative ceramics and functional ceramics. Through the compatibility and adjustment of different colorants, a variety of colors and effects can be achieved.

[0040] As a second limitation of the preparation method of the present invention, in step 2), when the ② casting method is adopted, the number of layers of the laminate is 10.

[0041] The above technical solution of the present invention is taken as a whole, and each step is closely related and influences each other, and they jointly determine the performance of the product.

[0042] The above technical solution has the following advantages or beneficial effects:

[0043] 1. The preparation method of the present invention is simple, the process is easy to control, the cycle is short, the prepared product meets people's demand for colored ceramics, and is easy to market and promote;

[0044] 2. The volume density of the alumina ceramic obtained by the present invention is ≥3.85g / cm 3 , flexural strength ≥400MPa, thermal conductivity ≥22W / (mk), the ceramic material has good coloring, is uniform and delicate, the product has good comprehensive performance, long life, and its performance is comparable to traditional alumina ceramics.

[0045] The embodiments of the present invention will be further described in detail below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 This is a physical picture of the colored alumina ceramic prepared in Example 1;

[0047] Figure 2 This is a SEM image of the colored alumina ceramic prepared in Example 1;

[0048] Figure 3 This is a physical picture of the colored alumina ceramic prepared in Example 3;

[0049] Figure 4 This is a SEM image of the colored alumina ceramic prepared in Example 3;

[0050] Figure 5 This is a physical picture of the colored alumina ceramic prepared in Example 4. DETAILED DESCRIPTION

[0051] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.

[0052] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified. Example 1

[0053] This embodiment prepares a dense and uniform colored alumina ceramic, the colored ceramic having color numbers R197, G33, and B98.

[0054] The material components are: Al2O3 (purity is more than 99.9%, average particle size D50 is 1-5μm) 98.8g, erbium oxide and ytterbium oxide 1g (the mass ratio of the two is 1:1), MnCO3 1g, PVB 1g, triethyl phosphate 2g, anhydrous ethanol 60g, and molten binder 10g.

[0055] The preparation process of the molten binder is carried out in the following steps:

[0056] S1. Preparation of sol: Add about 90 mL of ethanol to a beaker, slowly add 30 g of tetraethoxysilane (TEOS) to the ethanol, and stir with a stirrer at room temperature to form a uniform silicon precursor solution; add about 30 mL of deionized water and 1 mL of nitric acid dropwise as an acid catalyst, and continue stirring for 1 hour to promote the hydrolysis and condensation reaction of TEOS to form a uniform silica sol;

[0057] S2. Adding aluminum precursor: dissolving 10 g aluminum isopropanol (Al(OC3H7)3) in 20 mL ethanol to form a uniform aluminum precursor solution, slowly adding the obtained aluminum precursor solution dropwise to the above silica sol, and continuing stirring for 1 h to make the aluminum sol uniformly mixed and undergo hydrolysis and condensation reactions to form a composite sol containing aluminum;

[0058] S3, adding lithium precursor: taking 2g lithium nitrate (LiNO3) and dissolving it in 4mL deionized water to obtain a lithium precursor solution, slowly dropping the obtained lithium precursor solution into the above composite sol containing aluminum, and continuously stirring for 30min to make the lithium ions evenly distributed in the sol, thereby obtaining a lithium-containing sol;

[0059] S4. Rare earth doping: dissolve 3 g of erbium oxide and 2 g of ytterbium oxide in 10 mL of dilute nitric acid solution, heat slightly to accelerate dissolution (need to be done in a fume hood), and obtain a rare earth nitrate solution. Slowly drip the obtained rare earth nitrate solution into the above lithium-containing sol, and continue stirring for 2 h to ensure that the rare earth ions are evenly distributed in the sol to obtain a mixed solution;

[0060] S5, placing the obtained mixed solution in an electric constant temperature forced air drying oven and aging it at 40°C for 48 hours to make it gel-like, and then raising the temperature of the drying oven to 100°C and drying it for 10 hours to obtain a powdered glass powder precursor containing rare earth elements;

[0061] S6. Place the obtained precursor into a muffle furnace and sinter it according to the following process:

[0062] The first stage: heating from room temperature to 110 °C at a heating rate of 2 °C / min, and keeping the temperature for 150 min;

[0063] The second stage: heating from 110 ℃ to 400 ℃ at a heating rate of 2 ℃ / min, and keeping the temperature for 150 min;

[0064] The third stage: heating from 400 °C to 800 °C at a heating rate of 2 °C / min, keeping the temperature for 150 min, cooling to room temperature with the furnace, and obtaining the sintered product;

[0065] S7. The sintered product is ball-milled at 300 r / min for 10 h using a planetary ball mill. After the ball milling is completed, the obtained glass powder is sieved through a 200-mesh sieve and the product is collected, which is the molten binder.

[0066] The method for preparing colored alumina ceramics in this embodiment is as follows:

[0067] Step 1: Al2O3, erbium oxide and ytterbium oxide, MnCO3, PVB, triethyl phosphate and molten binder are weighed in proportion and placed in a ball mill, anhydrous ethanol is used as a liquid medium for wet mixing, anhydrous ethanol is added for ball milling, the ball-to-material ratio is 1:3, and the ball milling is carried out at a ball milling speed of 250 r / min for 30 minutes to obtain a slurry;

[0068] Step 2: The slurry obtained in step 1 is placed in a low-temperature oven at 80°C for drying, the dried slurry is collected and ground, the ground powder is passed through a 50-mesh sieve, and then the sieved powder is collected and bagged, and placed in a mold and dry-pressed into a sheet at 200MPa, and the diameter of the dry-pressed disc is 30mm;

[0069] Step 3: Place the dry-pressed disc formed in step 2 in a high-temperature sintering furnace, heat it from room temperature to 1200°C at a heating rate of 3°C / min, keep it warm for 4 hours, and cool it to room temperature with the furnace after sintering to obtain colored alumina ceramics.

[0070] The actual photo of the colored aluminum oxide obtained in this embodiment is as follows: Figure 1 As shown in the figure, it can be seen that the coloring is good, the color is uniform, delicate and bright. Figure 2 As shown in the figure, it can be seen that the alumina grains are dense and uniform, without obvious pores and bubbles. Example 2

[0071] This embodiment prepares a dense and uniform colored alumina ceramic, the colored ceramic having color numbers R203, G84, and B117.

[0072] The material components are: Al2O3 (purity of more than 99.9%, average particle size D50 of 1-5μm) 90g, erbium oxide and ytterbium oxide 0.5g (the mass ratio of the two is 1:1), MnCO3 0.5g, ethyl cellulose 0.5g, polyvinyl pyrrolidone 0.5g, anhydrous ethanol 50g, and molten binder 5g.

[0073] The preparation process of the molten binder is the same as that of Example 1.

[0074] The method for preparing colored alumina ceramics in this embodiment is as follows:

[0075] Step 1: Al2O3, erbium oxide and ytterbium oxide, MnCO3, ethyl cellulose, polyvinyl pyrrolidone, and molten binder are weighed in proportion and placed in a ball mill, and anhydrous ethanol is used as a liquid medium for wet mixing, and anhydrous ethanol is added for ball milling, with a ball-to-material ratio of 1:3, and the ball milling is performed at a ball milling speed of 300 r / min for 30 minutes to obtain a slurry;

[0076] Step 2: The slurry obtained in step 1 is placed in a low-temperature oven at 60° C. to dry, the dried slurry is collected and ground, the ground powder is passed through a 100-mesh sieve, and then the sieved powder is collected and bagged, and placed in a mold to dry-press into a sheet at 200 MPa, and the diameter of the dry-pressed disc is 30 mm;

[0077] Step 3: Place the dry-pressed disc formed in step 2 in a high-temperature sintering furnace, heat it from room temperature to 1200°C at a heating rate of 3°C / min, keep it warm for 4 hours, and cool it to room temperature with the furnace after sintering to obtain colored alumina ceramics. Example 3

[0078] In this embodiment, a dense and uniform colored alumina ceramic is prepared, and the colored ceramics with color numbers R189, G219, and B212 are prepared.

[0079] The material components are: Al2O3 (purity of more than 99.9%, average particle size D50 of 1 to 5 μm) 99.5 g, erbium oxide and ytterbium oxide 2 g (the mass ratio of the two is 1:1), NiO 2 g, hydroxypropyl methylcellulose 0.2 g, acrylate 1 g, anhydrous ethanol 70 g, and molten binder 8 g.

[0080] The preparation process of the molten binder is the same as that of Example 1.

[0081] The method for preparing colored alumina ceramics in this embodiment is as follows:

[0082] Step 1: Al2O3, erbium oxide and ytterbium oxide, NiO, hydroxypropyl methylcellulose, acrylate, and molten binder are weighed in proportion and placed in a ball mill, anhydrous ethanol is used as a liquid medium for wet mixing, anhydrous ethanol is added for ball milling, the ball-to-material ratio is 1:3, and the ball milling is performed at a ball milling speed of 200 r / min for 30 minutes to obtain a slurry;

[0083] Step 2: The slurry obtained in step 1 is placed in a low-temperature oven at 90°C for drying, the dried slurry is collected and ground, the ground powder is passed through a 200-mesh sieve, the sieved powder is then collected and bagged, and placed in a mold for dry pressing at 200 MPa into a sheet, the diameter of the dry-pressed disc is 30 mm;

[0084] Step 3: Place the dry-pressed disc formed in step 2 in a high-temperature sintering furnace, heat it from room temperature to 1200°C at a heating rate of 3°C / min, keep it warm for 4 hours, and cool it to room temperature with the furnace after sintering to obtain colored alumina ceramics.

[0085] The actual photo of the colored aluminum oxide obtained in this embodiment is as follows: Figure 3 As shown in the figure, it can be seen that the coloring is good, the color is uniform, delicate and bright, and the scanning electron microscope picture is as follows Figure 4 As shown in the figure, it can be seen that the alumina grains are dense and uniform, without obvious pores and bubbles. Example 4

[0086] In this embodiment, a dense and uniform colored alumina ceramic is prepared, and the colored ceramics with color numbers R177, G127, and B162 are prepared.

[0087] The material components are: Al2O3 (purity is more than 99.9%, average particle size D50 is 1-5μm) 98.8g, erbium oxide and ytterbium oxide 2g (the mass ratio of the two is 1:1), CrO3 1g, polyvinyl butyral ester 0.5g, propylene glycol methyl ether acetate 1g, anhydrous ethanol 70g, and molten binder 6g.

[0088] The preparation process of the molten binder is the same as that of Example 1.

[0089] The method for preparing colored alumina ceramics in this embodiment is as follows:

[0090] Step 1: Al2O3, erbium oxide and ytterbium oxide, CrO3, polyvinyl butyral ester, propylene glycol methyl ether acetate, and molten binder are weighed in proportion and placed in a ball mill, anhydrous ethanol is used as a liquid medium for wet mixing, anhydrous ethanol is added for ball milling, the ball-to-material ratio is 1:3, and the ball milling is performed at a ball milling speed of 300 r / min for 30 minutes to obtain a slurry;

[0091] Step 2: The slurry obtained in step 1 is placed in a vacuum degassing machine for degassing, the degassing time is 30 minutes, and the degassing pressure is 1.0 kPa; the degassing slurry obtained is introduced into a hopper, and the casting thickness is set to 150 μm, and the wet blank is obtained by casting on the casting machine, and the green porcelain strip is obtained by ventilation, heating and drying in the casting machine; the green porcelain strip is cut, and ten layers of strips are selected for lamination, the temperature is 80° C., and the pressure is maintained at 1000 psi for 60 minutes to obtain a green colored alumina ceramic substrate;

[0092] Step 3: Place the alumina ceramic substrate green body in step 2 in a high-temperature sintering furnace, heat it from room temperature to 1200°C at a heating rate of 3°C / min, keep it warm for 4 hours, and cool it to room temperature with the furnace after sintering to obtain colored alumina ceramics.

[0093] The actual photo of the colored aluminum oxide obtained in this embodiment is as follows: Figure 5 As shown in the picture, it can be seen that the coloring is good, and the color is uniform, delicate and bright.

[0094] The performance of the colored alumina alumina ceramic products provided in Examples 1-4 of the present invention was measured respectively, and the test results are shown in Table 1.

[0095] Table 1 Performance test items and test results of colored alumina ceramics

[0096]

[0097] It can be seen from Table 1 above that the colored alumina ceramics prepared by the present invention have better performance in terms of thermal conductivity and mechanical properties, and there is no significant change compared with traditional alumina ceramics. The present invention ensures that the related properties of the alumina ceramics do not fluctuate significantly while uniformly coloring the alumina ceramics, and has excellent comprehensive performance. Comparative Example

[0098] In order to explore the influence of the ingredients of colored alumina ceramics on the final ceramic properties, this comparative example carried out the following experimental processes. The preparation method of each group of experiments was similar to that of Example 1, and the only difference was that the ingredients were different.

[0099] Group A: The ingredients of colored alumina ceramics are similar to those of Example 1, except that sintering aids erbium oxide and ytterbium oxide are not added to the formula of this group.

[0100] Group B: The ingredients of colored alumina ceramics are similar to those of Example 1, except that the sintering aid in this group of formulas is erbium oxide.

[0101] Group C: The ingredients of colored alumina ceramics are similar to those of Example 1, except that the sintering aid in this group of formulas is ytterbium oxide.

[0102] Group D: The ingredients of colored alumina ceramics are similar to those of Example 1, except that the sintering aid in this group of formulas is yttrium oxide.

[0103] Group E: The ingredients of colored alumina ceramics are similar to those of Example 1, except that no molten binder is added to the formula of this group.

[0104] Group F: The ingredients of colored alumina ceramics are similar to those of Example 1, except that sintering aids erbium oxide and ytterbium oxide and molten binder are not added to the formula of this group.

[0105] Group G: The ingredients of colored alumina ceramics are similar to those in Example 1, except that the molten binder in this group of formulas is aluminoborosilicate glass powder, which is prepared by a preparation method publicly reported in existing literature (Chinese patent application number 2022101368119).

[0106] A series of performance tests were performed on the alumina ceramic materials prepared from Groups A to G, and the specific results are shown in the following table.

[0107]

[0108] Compared with aluminum borosilicate, aluminum-lithium-silicon glass powder has the following advantages as a molten binder: it matches the thermal expansion coefficient of alumina ceramics, thereby reducing the stress and cracks generated by ceramics during thermal cycles or temperature changes; it can provide better mechanical strength and toughness, because the addition of lithium ions can improve the structure of the glass material and reduce internal defects in the structure, thereby improving its ability to resist mechanical damage.

[0109] It can be seen from the above comparison groups that in the formation process of the colored alumina ceramics of the present invention, the molten binder can effectively adjust the sintering temperature of the alumina ceramics on the one hand, and on the other hand, it can cooperate with sintering aids and other materials to jointly affect the coloring effect and performance of the ceramic material.

[0110] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the claims of the present invention.

Claims

1. A dense and uniform colored alumina ceramic, characterized in that: The following components are included in parts by weight: 90-99.5 parts of alumina, 50-70 parts of anhydrous ethanol, 0.5-2 parts of sintering aid, 5-10 parts of molten binder, 0.5-2 parts of colorant, 0.2-1 parts of binder, and 0.5-2 parts of dispersant; The sintering aid is obtained by mixing erbium oxide and ytterbium oxide in a mass ratio of 1:1; The molten binder is lithium aluminum silicate glass powder, and its preparation process is carried out in the following steps: S1, preparation of sol: add 90mL of ethanol to a beaker, slowly add 30g of tetraethoxysilane to the ethanol, stir with a stirrer at room temperature to form a uniform silicon precursor solution; add 30mL of deionized water and 1mL of nitric acid dropwise as an acid catalyst, continue stirring for 1h to form a uniform silica sol; S2. Adding aluminum precursor: dissolving 10 g aluminum isopropanol in 20 mL ethanol to form a uniform aluminum precursor solution, slowly adding the aluminum precursor solution dropwise to the silica sol, and continuing stirring for 1 h to allow the aluminum sol to be uniformly mixed and undergo hydrolysis and condensation reactions to form a composite sol containing aluminum; S3, adding lithium precursor: dissolving 2 g of lithium nitrate in 4 mL of deionized water to obtain a lithium precursor solution; slowly adding the lithium precursor solution dropwise to the composite sol, stirring continuously for 30 min, so that the lithium ions are evenly distributed in the sol, to obtain a lithium-containing composite sol; S4. Rare earth doping: prepare a rare earth solution: dissolve 3 g of erbium oxide and 2 g of ytterbium oxide in dilute nitric acid to obtain a rare earth nitrate solution; Slowly add the rare earth nitrate solution into the lithium-containing composite sol and continue stirring for 2 hours to obtain a mixed solution; S5, placing the obtained mixed solution in an electric constant temperature air drying oven and aging it at 40°C for 48 hours to make it gel-like, and then raising the temperature of the drying oven to 100°C and drying it for 10 hours to obtain a powdered glass powder precursor containing rare earth elements; S6. Place the obtained precursor into a muffle furnace and sinter it according to the following process: The first stage: heating from room temperature to 110 °C at a heating rate of 2 °C / min, and keeping the temperature for 150 min; The second stage: heating from 110 ℃ to 400 ℃ at a heating rate of 2 ℃ / min, and keeping the temperature for 150 min; The third stage: heating from 400 °C to 800 °C at a heating rate of 2 °C / min, keeping the temperature for 150 min, cooling to room temperature with the furnace, and obtaining the sintered product; S7. The sintered product is ball-milled at 300 r / min for 10 h using a planetary ball mill. After the ball milling is completed, the obtained glass powder is sieved through a 200-mesh sieve and the product is collected, which is the molten binder.

2. A dense and uniform colored alumina ceramic according to claim 1, characterized in that: The colorant is a metal carbonate or a transition metal oxide.

3. A dense and uniform colored alumina ceramic according to claim 1, characterized in that: The binder is selected from at least one of polyvinyl alcohol, polyvinyl butyral, hydroxypropyl methylcellulose and ethyl cellulose.

4. A dense and uniform colored alumina ceramic according to claim 1, characterized in that: The dispersant is selected from at least one of acrylate, propylene glycol methyl ether acetate, polyvinyl pyrrolidone, BYK, and triethyl phosphate.

5. A method for preparing a dense and uniform colored alumina ceramic according to any one of claims 1 to 4, characterized in that: Follow the steps below in order: 1) Ingredients: Weigh Al2O3 powder, sintering aid, colorant, molten binder, adhesive and dispersant in proportion into a ball mill, add anhydrous ethanol and mill at a speed of 200-300 r / min for 30 min; 2) Molding: The molding step is carried out by the following ① dry pressing method or ② casting method: ① Dry pressing method: the slurry obtained in step 1) is placed in a low-temperature oven at 60-90°C for drying, the dried slurry is collected and ground, the ground powder is passed through a 50-200 mesh sieve, and then the sieved powder is collected and bagged, and placed in a grinding tool and dry pressed at 200 MPa to form a colored alumina ceramic green body, with a disc diameter of 30 mm; ② Casting method: After degassing, pour the ceramic slurry obtained in step 1) into a hopper, set the casting thickness to 150 μm, cast on a casting machine to obtain a wet blank, ventilate, heat and dry in the casting machine to obtain a raw ceramic strip, cut and stack to obtain a colored alumina ceramic green body; 3) Sintering: The ceramic green body formed in step 2) is placed in a high-temperature sintering furnace and sintered at 1200° C. for 4 hours to obtain colored alumina ceramics.

6. The method for preparing a dense and uniform colored alumina ceramic according to claim 5, characterized in that: In step 3), the heating rate of the sintering heating process is 3°C / min.

7. The method for preparing a dense and uniform colored alumina ceramic according to claim 5 or 6, characterized in that: In step 2), when the ② casting method is adopted, the number of layers of the laminate is 10.